2004
DOI: 10.1074/jbc.c300382200
|View full text |Cite
|
Sign up to set email alerts
|

Domain Analysis of the Calcium-activated Potassium Channel SK1 from Rat Brain

Abstract: Two small conductance, calcium-activated potassium channels (SK channels), SK2 and SK3, have been shown to contribute to the afterhyperpolarization (AHP) and to shape the firing behavior in neurons for example in the hippocampal formation, the dorsal vagal nucleus, the subthalamic nucleus, and the cerebellum. In heterologous expression systems, SK2 and SK3 currents are blocked by the bee venom toxin apamin, just as well as the corresponding neuronal AHP currents. However, the functional role and pharmacologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 37 publications
5
46
0
Order By: Relevance
“…The three-amino-acid motif in the S3-S4 loop of SK channels (SLV in rSK1, TYA in hSK1, SYA in SK2, and SYT in SK3) is an essential molecular determinant for apamin sensitivity. These data resolve the dichotomy that rSK1 is insensitive to apamin (11,12), yet has the same pore sequence as the apamin-sensitive hSK1. It is because rSK1 displays SLV in the S3-S4 loop that prevents binding of apamin.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…The three-amino-acid motif in the S3-S4 loop of SK channels (SLV in rSK1, TYA in hSK1, SYA in SK2, and SYT in SK3) is an essential molecular determinant for apamin sensitivity. These data resolve the dichotomy that rSK1 is insensitive to apamin (11,12), yet has the same pore sequence as the apamin-sensitive hSK1. It is because rSK1 displays SLV in the S3-S4 loop that prevents binding of apamin.…”
Section: Discussionsupporting
confidence: 62%
“…Amino acids 246 YA 247 / 213 LV 214 dictate apamin binding and block. Expression of homomeric rSK1 subunits does not produce functional channels (11,12,15). Functional channel current is produced on expression of a chimeric channel (rSK1*), where the carboxyl terminus of rSK1 is replaced by that from rSK2 (11).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All three KCNN ␣-subunits were found to be expressed in MCCs, giving rise to a bisigmoidal dose-response curve of apamin on slow tail currents. Different SK channel isoforms are characterized by distinct apamin sensitivities, with SK2 being most sensitive (IC 50 ϭ 60 -70 pM), SK3 showing an intermediate sensitivity (IC 50 ϭ 0.63-6 nM), and rat/mouse SK1 being rather insensitive (Ishii et al, 1997;Grunnet et al, 2001;Benton et al, 2003;D'hoedt et al, 2004;Weatherall et al, 2011). Heterologous expression studies (Ishii et al, 1997) have shown that SK channels might be heteromeric in nature, giving rise to channels with intermediate apamin sensitivities.…”
Section: Sk Channel Expression and Its Role In Firing At Rest And Durmentioning
confidence: 99%
“…IK channels are insensitive to these blockers. In the rat, it seems likely that SK1 subunits cannot form functional channels by themselves (Benton et al, 2003;D'hoedt et al, 2004;Monaghan et al, 2004). However, they can form functional channels in combination with SK2 (Benton et al, 2003).…”
Section: Introductionmentioning
confidence: 99%